The Sacrality of Things: An Inquiry into Divine Materiality in the Christian Middle Ages - Bynum, Caroline Walker (Irish theological quarterly, 2013)
Students of comparative religion, cognitive scientists, art historians, and historians sometimes use paradigms from non-western religions to raise questions about the role of material objects in Christianity. Recently, such discussion has focused on images and controversies about them. This article argues that the most important material manifestation of the holy in the western European Middle Ages was the Eucharist and suggests both that understanding it is enhanced by the use of comparative material and that considering it as a case study of divine materiality leads to a more sophisticated formulation of comparative paradigms.